Nerve growth factor sensitizes adult sympathetic neurons to the proinflammatory peptide bradykinin - Vivas, Oscar; Kruse, Martin; Hille, Bertil (The Journal of neuroscience, 2014)
Levels of nerve growth factor (NGF) are elevated in inflamed tissues. In sensory neurons, increases in NGF augment neuronal sensitivity (sensitization) to noxious stimuli. Here, we hypothesized that NGF also sensitizes sympathetic neurons to proinflammatory stimuli. We cultured superior cervical ganglion (SCG) neurons from adult male Sprague Dawley rats with or without added NGF and compared their responsiveness to bradykinin, a proinflammatory peptide. The NGF-cultured neurons exhibited significant depolarization, bursts of action potentials, and Ca(2+) elevations after bradykinin application, whereas neurons cultured without NGF showed only slight changes in membrane potential and cytoplasmic Ca(2+) levels. The NGF effect, which requires trkA receptors, takes hours to develop and days to reverse. We addressed the ionic mechanisms underlying this sensitization. NGF did not alter bradykinin-induced M-current inhibition or phosphatidylinositol 4,5-bisphosphate hydrolysis. Maxi-K channel-mediated current evoked by depolarizations was reduced by 50% by culturing neurons in NGF. Application of iberiotoxin or paxilline, blockers of Maxi-K channels, mimicked NGF treatment and sensitized neurons to bradykinin application. A calcium channel blocker also mimicked NGF treatment. We found that NGF reduces Maxi-K channel opening by decreasing the activity of nifedipine-sensitive calcium channels. In conclusion, culture in NGF reduces the activity of L-type calcium channels, and secondarily, the calcium-sensitive activity of Maxi-K channels, rendering sympathetic neurons electrically hyper-responsive to bradykinin.